Factors Associated with the Incidence of Hypotension in Patients With Spinal Anesthesia - Gani, Evita; Triyudono, Danang; Lintang Suryani, Roro (Global Indonesia Health Care (GOICARE), 2024)
Background: Spinal anesthesia is a regional anesthetic that functions in inhibiting the spinal nerves in surgical attempts. Spinal anesthesia also has complications, one of which is hypotension. Purpose: to determine the factors of hypotension in patients with spinal anesthesia at Mayjend Hospital. H. M. Ryacudu North Lampung. Methods: using analytic correlation with a cross sectional approach. Sample technique with purposive sampling. The number of samples was 56 respondents. The study used observations containing post-anesthesia data including age, gender, BMI, and type of drug and the incidence of hypotension. Findings: The age of the respondents was mostly in the early adult category, 21 (37.5%). Male gender is 28 (50%) and female is 28 (50%), the majority of BMI with normal category is 24 (42.9%), the type of anesthesia is Bupivacaine 28 (50%) and Levobupivacain 28 (50%).There is no relationship between age, gender and type of drug with hypotension with p_value>0.05 Conclusion: there is a relationship between BMI and hypotension in post-spinal anesthesia patients at RSD Mayjend. H. M. Ryacudu North Lampung with a p-value of 0.00 (<0.05).